2016
DOI: 10.1016/j.ijrobp.2015.10.055
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Hypofractionated Protracted Radiation Therapy and Dose Escalation for Prostate Cancer: Do Dose and Overall Treatment Time Matter?

Abstract: SummaryThis report compares, retrospectively, the 5-year treatment outcomes and toxicity rates of 2 sequential dose escalation regimens of twiceweekly 4 Gy/fractions hypofractionated intensity modulated radiation therapy in patients with localized prostate cancer. A single 4-Gy additional fraction in patients treated with 14 Â 4 Gy resulted in a similar and minimal acute toxicity, in worse moderate to severe urinary and gastrointestinal late effects, but a significantly better biochemical control.Purpose: This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…Besides, many patients presented with oligometastasis, and longer survival durations were often observed among them, thus the short fractionation schedules, which sometimes required the need for retreatment (18), were less adequate. Our results suggested the use of intensive dose prescription, which was consistent with the results in hepatocellular cancer (HCC), renal and prostate cancers (19)(20)(21)(22). Kim et al (20) selected HCC patients who were followed up for at least 1 year and a positive dose-response relationship was observed.…”
Section: Discussionsupporting
confidence: 89%
“…Besides, many patients presented with oligometastasis, and longer survival durations were often observed among them, thus the short fractionation schedules, which sometimes required the need for retreatment (18), were less adequate. Our results suggested the use of intensive dose prescription, which was consistent with the results in hepatocellular cancer (HCC), renal and prostate cancers (19)(20)(21)(22). Kim et al (20) selected HCC patients who were followed up for at least 1 year and a positive dose-response relationship was observed.…”
Section: Discussionsupporting
confidence: 89%
“…Next day plates were irradiated with 0 Gy, 2 Gy, 4 Gy and 6 Gy of X-rays (Yxlon Y.TU 320; 200 kV X-rays, dose rate 1.3Gy/min at 20 mA, filtered with 0.5 mm Cu). We have irradiated cells with a single dose of 4Gy for some of our experiments, as several clinical studies suggested the safety and efficiency of moderate hypofractionation (doses of 2.5-4 Gy per fraction) for prostate cancer [77][78][79]. After the irradiation, cells were left in the humidified CO2 incubator for 7 to 10 days.…”
Section: Clonogenic Cell Survival Assaymentioning
confidence: 99%
“…Whole pelvic irradiation was delivered in two patients followed by a hypofractionated boost of 24 Gy in 6 fractions. Details concerning treatment schedules as well as dose constraints for inverse planning have been previously described [13][14][15]. All patients were treated with a volumetric modulated arc therapy on a Novalis TX linear accelerator with a High Definition Millennium HD120 MLC equipped with an on-board imaging device (OBI) and À6 degrees of freedom robotic couch.…”
Section: Patients and Treatment Characteristicsmentioning
confidence: 99%